1999
DOI: 10.1557/s109257830000332x
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thin films Polarity of Group III Nitrides

Abstract: Thin films of GaN grown by MOCVD on (0001) sapphire were studied by transmission electron microscopy in order to correlate the observed extended defects with crystal polarity of the films. We propose relatively simple and unambiguous method of polarity determination for wurtzite group III nitrides based on the dependence of the intensity of diffracted beams upon thickness of the specimen. Due to the dynamic scattering by polar structure, the convergent beam electron diffraction patterns lose inversion symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…The smooth films grown under optimum or nitrogen-rich conditions by MOCVD and at optimum temperature by PLD have shown Ga-face (0001) polarity [11]. The same Ga-polarity has been found for the wurtzite grains with c-axis normal to the substrate surface as shown in the left inset of the Fig.…”
Section: Disscusionsupporting
confidence: 68%
See 2 more Smart Citations
“…The smooth films grown under optimum or nitrogen-rich conditions by MOCVD and at optimum temperature by PLD have shown Ga-face (0001) polarity [11]. The same Ga-polarity has been found for the wurtzite grains with c-axis normal to the substrate surface as shown in the left inset of the Fig.…”
Section: Disscusionsupporting
confidence: 68%
“…4, the hexagonal grains with c-axis normal to the substrate surface and those with the inclined c-axis would have opposite face polarity, if the latter grains are nucleated on the cubic phase faces and the polarity is preserved across the phase interface. We have used CBED to determine the polarity of the grains [11]. Due to dynamic electron beam scattering by the non-centrosymmetric specimen, the CBED pattern loses the inversion symmetry.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MOVPE, usually Ga-polar (+c polar) GaN has been epitaxially grown with smooth surfaces. Device quality films grown by MOVPE have been reported to have Ga-polarity [1]. On the other hand, N-polar (-c polar) GaN has been reported to have rough surfaces [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the open cores in epitaxial polar materials can be correlated to the nucleation stage or to the impurities incorporated during the growth stage. The occurrence of inversion domains (IDs) in unintentionally doped GaN layers is often observed in MOVPE [9]. In addition, it has been reported that an excess amount of Mg causes IDs in GaN films [10].…”
mentioning
confidence: 99%